Relugolix’s impact on endometriosis-associated pain and quality of life: a meta-analysis of EHP-30 outcomes - Xie, Jiani; Ni, Xiaorong; Huang, Qunhuan; Guo, Ying (Frontiers in Endocrinology, 2025)
BackgroundRelugolix offers a promising alternative for endometriosis-associated pain, yet its comprehensive impact on health-related quality of life (HRQoL), particularly as measured by the disease-specific EHP-30 questionnaire, remains underexplored.MethodsWe conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) investigating relugolix for endometriosis-associated pain, with a primary focus on HRQoL assessed by the Endometriosis Health Profile-30 (EHP-30). Data extracted included EHP-30 domain scores changes and proportion of EHP-30 Pain Domain Responders, along with intervention details, control type, and follow-up duration.ResultsFive RCTs were included. Overall, relugolix significantly improved EHP-30 Pain domain scores (MD = 6.77, 95% CI: 3.15 to 10.39, p=0.0002) but showed substantial heterogeneity (I²=90.7%). Subgroup analysis by control type showed significant differences (p<0.0001): Relugolix was highly effective against placebo (MD = 15.31, 95% CI: 12.18 to 18.45) and placebo-matching combination therapy (MD = 8.86, 95% CI: 5.03 to 12.69), but numerically less effective than leuprorelin (MD = -3.79, 95% CI: -6.27 to -1.31). Relugolix significantly increased EHP-30 Pain Domain Responders (OR = 3.245, 95% CI: 2.496; 4.219, p < 0.0001). For other EHP-30 domains, relugolix demonstrated significant improvements in Emotional Well-being (MD = 5.71, 95% CI: 1.87; 9.55, p=0.0036), Social Support (MD = 6.40, 95% CI: 0.88; 11.93, p=0.0231), and Self-image (MD = 6.00, 95% CI: 1.03; 10.96, p=0.0179) compared to placebo.ConclusionOral relugolix significantly improves EHP-30 pain domain scores and patient response rates in endometriosis, particularly when compared to placebo. It also positively impacts emotional well-being, social support, and self-image.